Study on freeboard temperature profile during combustion of rice husk in a fluidized bed combustor - Rozainee, M.; Ngo, S.P.; Salema, A. A.; Tan, K.G (Faculty of Chemical Engineering & Natural Resources, 2008)

(untitled)
In this paper, the temperature profile while firing rice husk in a fluidized bed combustor was investigated. The experiment was carried out in a 210 mm I.D. non insulated fluidized bed combustor with a height of 2000 mm. The experiments were carried out in two sets; firstly without any secondary burner and secondly with one and two secondary burners in the freeboard region and its effect on temperature was studied. The results without any secondary burner showed that the temperature reduces sharply along the height of the combustor with fluctuation in freeboard temperature. The reason was heat loss to surrounding due to non insulation of the fluidized bed combustor and run off flue gas . However, improvement or almost steady freeboard temperature profile was observed with addition of one and two secondary burners in the freeboard region. In addition to this, the high temperature (around 700Â°C) could help in burning off the carbon in the rice husk ash during elutriation from fluidized bed. Hence, freeboard region could be made as secondary combustion zone in obtaining high quality white siliceous ash.